PENERAPAN METODE ARSITEKTUR KESEHARIAN DALAM PERANCANGAN DESAIN MEETING POINT DI GUNUNG SAHARI, JAKARTA PUSAT - Meylina, Scholastica Violetha; Yuono, Doddy (Jurusan Arsitektur dan Perencanaan, 2024)
Golden Truly Mall is a place for recreation, a place to eat, a gathering place for various groups of people both from the surrounding area and outside because of its strategic location, in the city center, and close to TransJakarta transportation. Based on the results of a qualitative survey of the surrounding community, there are still many who feel they have missed the